Symmetry reductions, explicit solutions, convergence analysis and conservation laws via multipliers approach to the Chen-Lee-Liu model in nonlinear optics - Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abdullahi; Bayram, Mustafa; Baleanu, Dumitru (World Scientific Publ Co Pte Ltd, 2019)
In this paper, symmetry analysis is performed for the nonlinear Chen-Lee-Liu equation (NCLE) arising in temporal pulses. New forms of explicit solutions of the equation are constructed using the optimal systems by applying the power series solutions (PSS) technique and the convergence of the PSS is investigated. Finally, the conservation laws (Cls) of the model is studied using the multiplier approach.
Keywords: Symmetry analysis; power series solutions; convergence analysis; conservation laws